(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Evaluation of standard preventive practices of nurses at Hoa Binh general hospital in 2021 Subject and method: The cross-sectional descriptive study was conducted with 284 nurses working at Hoa Binh General Hospital from 03/2021 to 12/2021 Results: Nurses practicing hand hygiene account for a high proportion of work content. Still, 30,6% of nurses occasionally use face shields/goggles when there is a risk of splashing/splashing blood/ fluids of a sick person and 28,9% wear gowns when at risk of infection. The proportion of hospital nurses who achieved the practice of some standard preventive content accounted for 59,6%. Conclusion: The proportion of nurses practicing standard prevention by job accounts for a low proportion of work contents.